2019
DOI: 10.1039/c8nj04074e
|View full text |Cite
|
Sign up to set email alerts
|

Discrete mononuclear and dinuclear compounds containing a MoO22+core and 4-aminobenzhydrazone ligands: synthesis, structure and organic-solvent-free epoxidation activity

Abstract: New aroylhydrazone molybdenum(vi) complexes have been synthesized, characterized and used as (pre)catalysts for epoxidation of cyclooctene using aqueous TBHP as the oxidant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…For dinuclear structures absorption bands in the range of 870 -900 cm -1 confirm that the coordination sphere of molybdenum is completed by the nitrogen atom from the neighbouring complex molecule, as already noticed for similar compounds. [8,9] For the complex 2•MeCN, absorption maximum characteristic for MeCN was not noticed in the IR spectrum, while the band at 2340 cm -1 was present in the spectrum of 3•MeCN. The presence of the MeCN in 2•MeCN was later confirmed by TG analysis.…”
Section: Preparation Spectral Characterization and Thermal Behaviourmentioning
confidence: 92%
See 2 more Smart Citations
“…For dinuclear structures absorption bands in the range of 870 -900 cm -1 confirm that the coordination sphere of molybdenum is completed by the nitrogen atom from the neighbouring complex molecule, as already noticed for similar compounds. [8,9] For the complex 2•MeCN, absorption maximum characteristic for MeCN was not noticed in the IR spectrum, while the band at 2340 cm -1 was present in the spectrum of 3•MeCN. The presence of the MeCN in 2•MeCN was later confirmed by TG analysis.…”
Section: Preparation Spectral Characterization and Thermal Behaviourmentioning
confidence: 92%
“…This behaviour is well established in previous works. [8,9,22] Regarding the geometry of the ligand and the coordination sites, all analysed complexes ultimately possess the same tautomeric form and overall shape. Bond lengths (Table S3) suggest enol-imino form in the hydrazide functional group, as well as enolate form of chelating hydroxyaryl unit.…”
Section: Crystallographic Studymentioning
confidence: 94%
See 1 more Smart Citation
“…In the proposed quest, our research follow-up was to obtain efficient molybdenum epoxidation catalysts containing benzaldehyde-based hydrazones (Scheme 1). The choice of ligands lies in the fact that the similar molybdenum complexes showed good activity and were classified as efficient catalytic systems [11][12][13]. In the presented research, the stress was on the use of 2-hydroxy-benzhydrazide derivatives, that could provide catalytically active molybdenum complexes.…”
Section: Introductionmentioning
confidence: 99%
“…The use of chlorinated solvents such as dichloroethane (DCE), a highly toxic solvent, has to be avoided [ 15 ]. In the research group, the processes have been found to be active without organic solvent using complexes with tridentate ligands [ 16 , 17 , 18 , 19 , 20 ] or polyoxometalates (POMs) [ 21 , 22 , 23 ], giving a first step towards a cleaner process. The oxidant used in this case is tert -butyl hydroperoxide (TBHP) in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%